Bioremedial effect of turmeric (Curcuma longa) on haematological and biochemical parameters against fenvalerate induced toxicity in air-breathing fish Clarias batrachus - Pratibha Kumari; Dilip Kumar Paul (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
Indiscriminate use of insecticides has increased many folds in the recent times. Farmers for the better yield of crops, are widely utilising the pesticides. These pesticides through agricultural run offs have reached the surface water like ponds and has contaminated the flora and fauna of it. Fish is the animal which are extensively cultivated in these ponds. Humans are consuming these fishes as food as they have high nutritious value. These contaminated fish if consumed by the human has caused various health hazards to humans. The present research work is therefore focused to know the bioremedial effect of turmeric on fenvalerate induced toxicity in fish Clarias batrachus. Fenvalerate EC 20% (pyrethroid) was administered directly in water contained in aquarium at the dose of 0.92 ppm and observed for 96 hours after the dose calculation through LC50. Thereafter, aqueous rhizome extract of Turmeric was administered orally, daily by gastric intubation method at the dose of 100 mg/Kg body weight per day for 15 days. The study reveals that after the exposure of fenvalerate, there was significant damage at the haematological and biochemical levels in fish Clarias batrachus. But, after the administration of rhizome extract of turmeric, there was significant normalisation in the haematological and biochemical levels in fish. This denotes that turmeric not only possesses ameliorating and rejuvenating property but also maintains the normal functioning of the body of the fish. Thus, it proves to be one of the best antidote against fenvalerate induced toxicity.